Efficacy of 27-Gauge Vitrectomy with Internal Limiting Membrane Peeling for Epiretinal Membrane in Glaucoma Patients - Masaaki Yoshida; Hiroshi Kunikata; Shiho Kunimatsu-Sanuki; Toru Nakazawa (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of epiretinal membrane (ERM) surgery for patients with ERM and glaucoma. Methods. We reviewed the medical records of 20 consecutive ERM patients with glaucoma, who underwent 27-gauge microincision vitrectomy surgery (27GMIVS) with internal limiting membrane (ILM) peeling. The preoperative and 6-month postoperative visual field was tested with the Humphrey Field Analyzer (HFA) 24-2 program. Changes in threshold sensitivity in the HFA test points were analyzed point-by-point, with points classified into groups based on sensitivity as abnormal (less than 5th percentile in pattern deviation) or normal (all other points) and based on location as central (12 central points) or peripheral (all other points) with a linear mixed-effects model. Results. Visual acuity and mean deviation improved postoperatively (P<0.001 for both) in all patients. Threshold sensitivity in central or peripheral points that were abnormal preoperatively improved postoperatively (P=0.006 or P<0.001, respectively). Threshold sensitivity also improved in the central normal test points (P=0.03), but not in the peripheral normal points (P=0.12). Conclusion. Visual acuity improved, and there was no visual field progression, after ERM surgery in glaucomatous eyes during a 6-month postoperative follow-up, suggesting that ERM and ILM removal using 27GMIVS may be effective even in glaucomatous eyes.